Mustafa Kemal Atatürk: The First Gender Champion - Muhammed Ali Alkış; Océane Van Geluwe (International Journal of Nuclear Security, 2025)
The founder of the modern, secular nation-state of the Turkish Republic, Mustafa Kemal Atatürk, transformed the Ottoman Empire into the nation-state of Türkiye. His visionary approach focused on secularization and nation-state building, which established him as a true “gender champion” long before such a term had meaning in the current global agenda. With the support of Turkish women during and after the War of Independence, he committed himself to increasing all citizens’ welfare, focusing on gender equality and breaking the traditional gender barriers. His reforms resulted in the rapid modernization of the Turkish Republic, and Turkish women took a leading role in this process. Thanks to these developments, Türkiye inaugurated its first nuclear power plant at its centennial after many failed attempts. In this article, we will analyze his reforms that addressed inequalities in traditional gender roles and reinforced the position of Turkish women in creating a modern society. Thanks to these reforms in the Republic’s early days, Turkish women have an active and crucial role in policymaking and implementation processes in critical institutions. The article also highlights the relationship between Atatürk’s vision of gender equality and the modern concept of being a gender champion.
Keywords: Atatürk; gender champion; Türkiye; gender equality; nuclear field